Lingodhbhav-murti - Temples of India Project Team (Jio Institute, 2024)
This is a depiction of Shiva in the form of lingodhbhav-murti. Stella Kramrisch described this particular image from Harṣha: ‘In the universal night the pillar there was nothing; fiery pillar appeared above the waters. Other than it had no beginning no end. Brahmā flew into the empyrean and failed to reach its top; Viṣnu dived into the depth of the sea and failed to find its bottom. The two great gods thereupon submit and become the acolytes of the Fiery Pillar. The Fiery Pillar is in its splendour. to its greatness and Śiva; he reveals himself. The stele is traversed in its middle by the Fiery Pillar. On the left Brahmā is seen soaring upwards; he is also seen standing, his self-appointed mission unfulfilled, an attendant divinity of the Fiery Pillar. To the right of the Pillar, Viṣnu, blowing his conch, hurls himself downward with the same result; he becomes an acolyte of the Pillar and his standing image swings in the same rhythm as the image of Brahmā. The top of the slab, the high region traversed by the pillar, is a palpitating mass of movement and its shapes are Hamsa-birds and celestial spirits. The vision of the flaming pillar has been given form in this image competently though not adequately; the form is sleek and slight but succeeds in translating the Fiery Pillar into the trunk of the Tree whose branches are Brahmā, Viṣnu and the celestial host.’ (Hindu Temples, vol 2, Plate LXVII, page 402). This is one of the most iconic and celebrated images of Lingodbhava Murti, reputed for the delicacy of the figures, sense of movement and visual impact. In the incorporative landscape of Harsha Hill, having shrines dedicated to various deities, this image marks the Shaiva domination and supremacy at the complex.